Impact of Corporate Social Responsibility Funds From PT. Telkom Indonesia on MSMEs Development in Padang City: an Islamic Economic Perspective - Wira, Ahmad; Desya, Finasmi; Lubis, M Zaky Mubarak; Subagio, Mukhamad Hadi Musolin; Augusna, Wahyuni Lely (IKONOMIKA, 2022)
Micro, small, and medium enterprises (MSMEs) often borrow additional funds from third parties to develop their business, for example, corporate social responsibility (CSR) funds from state-owned companies such as PT. Telkom Indonesia (hereafter referred to as Telkom). This quantitative study aimed to ascertain the impact of CSR funds from Telkom on the development of MSMEs, especially those in the trade sector, in Padang City from an Islamic economic perspective. The data used in this study are primary data obtained through questionnaires filled by 52 MSMEs in the trade sector in Padang City, and secondary data, obtained from official documents from the Central Statistics Agency. Sampling and determination of the number of samples were achieved using a random sampling technique. The data analysis technique in this study used descriptive statistical analysis and inferential statistics through an analytical tool, namely, the Wilcoxon test. The results revealed a positive and significant impact on the CSR program of Telkom in developing MSMEs in the trade sector in Padang City from the perspective of Islamic economics. This positive and significant impact is evident in the changes in the income of MSMEs in the trade sector in Padang City, which increased by around 1–3 million rupiah after receiving CSR funds from Telkom since 2016. From the perspective of Islamic economics, the implementers of Telkom’s CSR fund program in the MSME trade sector in Padang City have adopted the basic principles of Islamic economic development, namely, the principles of responsibility and justice.